Series of thematic maps on biophysical and socioeconomic status of Malawi to guide targeting of agricultural technologies - Sonder, Kai; López Ridaura, Santiago (International Maize and Wheat Improvement Center, 2023)
Status and trends of mixed farming systems, targeting, data visualization.